1983
DOI: 10.1088/0022-3727/16/7/001
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature visible distributed-feedback colour centre laser

Abstract: The distributed-feedback (DFB) colour centre laser is described. The DFB laser action at 680 nm is observed by pumping on LiF crystal containing F2 centres with the fringes formed by the interference of two coherent light beams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…Next, we examined to fabricate a DFB F 2 color center laser using the holographic micrograting arrays encoded by interfered infrared femtosecond laser pulses. Oscillation of DFB F 2 color center laser in LiF was already reported by Kurobori et al [11]: however, the cavity of their DFB laser consisted of the transiently induced grating structure. There was no way to produce permanent gratings inside LiF.…”
Section: Resultsmentioning
confidence: 71%
“…Next, we examined to fabricate a DFB F 2 color center laser using the holographic micrograting arrays encoded by interfered infrared femtosecond laser pulses. Oscillation of DFB F 2 color center laser in LiF was already reported by Kurobori et al [11]: however, the cavity of their DFB laser consisted of the transiently induced grating structure. There was no way to produce permanent gratings inside LiF.…”
Section: Resultsmentioning
confidence: 71%
“…The construction of DFB lasers using F A (II) and N 2 CCs in KCl and F 2 CCs in LiF crystals was reported by G.C. Bjorklund 11 and Kurobori et al 12,13 . However, poor thermoand photo-stability were limiting factors in these crystals, and thus the lifetime of these lasers was short.…”
Section: Introductionmentioning
confidence: 89%
“…Studies on the equilibrium dynamics of the aggregate centers showed the possibility of provide a selective depopulation of one of the species [21]. The efficiency of the lithium fluoride optical pumping cycle allows a number of applications such as waveguides [22]- [27], color center lasers [28], including those with distributed feedback [29] periodic photorefractive structures [30] and even radiation detectors [31]. Radiation detectors are particularly interesting for imaging with confocal laser-scanning-microscopy using fluorescent excitation, allowing better resolution than conventional techniques and greater applicability in samples.…”
Section: Effects Of Birefringence On the Electromagnetic Guidance Of mentioning
confidence: 99%